The siege of Washington the untold story of the twelve days that shook the Union - Lockwood, John 1949-; Lockwood, Charles 1948-2012 (Oxford Univ. Press, 2011)
On April 14, 1861, Washington was 'put into the condition of a siege', declared Abraham Lincoln. Located 60 miles south of the Mason-Dixon Line, the nation's capital was surrounded by the slave states of Maryland and Virginia. With no fortifications and only a handful of trained soldiers, Washington was an ideal target for the Confederacy. This book tells the story from the perspective of leading officials, residents trapped inside the city, Confederates plotting to seize it, and Union troops racing to save it, capturing with brilliance and immediacy the precarious first days of the Civil War.